ANALISIS PEMBACAAN METER OTOMATIS LISTRIK DENGAN MENGGUNAKAN JARINGAN KOMUNIKASI - Rinna Hariyati (Sekolah Tinggi Teknik PLN, 2015)
KWH meter system of Automatic Meter Reading or hereafter will be referred to the kWH meter AMR is a recording system of electric energy meter is done automatically and remotely.Communication data sent by the kWH meter AMR of PT PLN (Persero) Jakarta and Tangerang Distribution using SMS modem which interfacing kWHmeterselectronic withwireless telecommunications networks. kWH meter AMR have features other than noting the energy used, also noting the voltage, electric current, power factor(cos ϕ), and as well as the use of electricity meters in record-keeping more quickly. Thus the PT PLN (Persero) Distribution can perform distribution network management (DNM) that makes it easier in terms of channeling energy into customers and monitoring the electric energy usage by customers. The results of the analysis of kWh meter AMR system can reduce losses caused by abnormalities in the distribution network system. SMS telemetry signal communication with the modem is unstable and often fail withdrawal data. To overcome the problem of the use of the old modem, the modem needs to be replaced with GPRS / LTE user ready. However, the use of power line communication (PLC) as a data transmission network to reduce reliance on mobile telecommunications networks.